STUDI KONEKTIVITAS ANTAR MODA ANGKUTAN UMUM DI KAWASAN INTERMODA BSD CITY, KABUPATEN TANGERANG - Sonia Azmy; Regina Suryadjaja; B. Irwan Wipranata; Suryadi Santoso (Jurusan Arsitektur dan Perencanaan, 2023)
Cities continue to experience unavoidable developments, both from an economic, social and cultural perspective as reflected in an increase in population and activity in urban areas. One example of activities in urban areas is people who want to do mobility from one place to another in order to fulfill their activity objectives. It's the same with the people in Tangerang Regency who live in Cisauk District and Pagedangan District. To meet this need, an area called